Penatalaksanaan Radioterapi Kanker Duodenum Di Instalasi Cancer Center Santosa Hospital Bandung Kopo - Andry Putra Wijaya; I Putu Eka Juliantara; Indra Mulia Utama (Jurnal Ilmu Kesehatan dan Gizi, 2024)
The duodenum is one of the three main parts of the small intestine and is shaped like the letter C which connects the stomach to other parts of the small intestine. Anatomically, the duodenum is located in the epigastric and umbilical regions (Corwin, 2009)